Exchange Rate Resilience, Capital Expenditure, and Capital Structure: Mediating Effects of Flexibility, Hedging, Liquidity - Sebastian Sebastian; Nur Afifah; Mustaruddin Mustaruddin; Titik Rosnani (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
Exchange rate volatility constitutes one of the most pervasive sources of financial uncertainty for non financial corporations engaged in international trade, foreign currency borrowing, and cross border investment. While prior research has examined exchange rate exposure, corporate hedging, liquidity management, and capital structure individually, no systematic synthesis has integrated these elements under the unifying lens of exchange rate resilience the firm level capacity to withstand and adapt to currency shocks while preserving strategic and financial continuity. This study presents a Systematic Literature Review (SLR) following the PRISMA 2020 framework, drawing on Scopus indexed Q1 and Q2 publications from 2016 to 2026. From an initial pool of 601 records identified through 11 targeted keyword combinations via the Watase Uake platform, 46 studies met all inclusion criteria after rigorous multi stage screening. The review synthesizes evidence on three mediating mechanisms  operational flexibility, hedging activity, and firm liquidity  through which exchange rate resilience influences capital expenditure (CapEx) and capital structure decisions. Findings reveal that hedging consistently reduces cash flow volatility, lowers financing costs, and supports investment continuity; firm liquidity functions as an absorptive buffer; and operational flexibility provides adaptive capacity. This study contributes a testable conceptual model and structured future research agenda for resilience oriented corporate finance.